General synthesis of single atom electrocatalysts via a facile condensation–carbonization process. Issue 48 (7th December 2020) - Chen, Weiming; Luo, Xuanli; Slater, Thomas J. A.; Zhou, Yongfang; Ling, Sanliang; Bao, Rui; Alves Fernandes, Jesum; Wang, Jianshe; Shen, Yi
Abstract : We report a synthetic protocol for synthesizing SAECs via a condensation–carbonization process, where furfural and cyanamide were polymerized in the presence of PS NSs and metal ions, followed by a pyrolysis to N-doped carbon nanosheet supported SAECs. Abstract : The general and cost-effective synthesis of single atom electrocatalysts (SAECs) still remains a great challenge. Herein, we report a general synthetic protocol for the synthesis of SAECs via a simple condensation–carbonization process, in which furfural and cyanamide were condensation polymerized in the presence of polystyrene nanospheres and metal ions, followed by a pyrolysis to N-doped carbon nanosheet (NCNS) supported SAECs. Six types of SAECs containing platinum, palladium, gold, nickel, cobalt and iron were synthesized to demonstrate the generality of the synthesis protocol. This methodology affords a facile solution to the trade-off between support conductivity and metal loading of SAECs by optimizing the ratio of carbon/nitrogen precursors, i.e., furfural and cyanamide. The presence of single metal atoms was confirmed by high-angle annular dark field scanning transmission electron microscopy and X-ray absorption fine structure measurements. The three-dimensional distribution of single platinum atoms was vividly revealed by depth profile analysis using a scanning transmission electron microscope. The resulting SAECs showed excellent performance for glycerol electro-oxidation and water splitting in alkaline solutions. Notably, Pt/NCNSs possessed an unprecedent mass-normalized current density of 5.3 A per milligram of platinum, which is 32 times that of the commercial Pt/C catalyst. Density functional theory calculations were conducted to reveal the adsorption behavior of glycerol over the SAECs. Using Ni/NCNSs and Co/NCNSs as anodic and cathodic electrocatalysts, we constructed a solar panel powered electrolytic cell for overall water splitting, leading to an overall energy efficiency of 8.8%, which is among the largest solar-to-hydrogen conversion efficiencies reported in the literature.